Concept creation in action: Internet space as a meteorological pressure system - Dovydaitis, Gytis (Creativity Studies, 2023)
The spatiality of the Internet is a complex phenomenon presupposing a wide range of ideas: that there are different environments which can be characterized, that there are subjects moving within them, that these spaces are being employed for certain ends by their users, and much more. However, various spatial descriptions of the Internet most of the time observe it as a part of a larger spatial architecture, not as a spatial architecture itself. This paper employs radical concept creation machinery conceptualized by Gilles Deleuze and Félix Guattari in What Is Philosophy? (first published in 1991), principles of paralogistic thinking proposed by Jean-François Lyotard and divergent thinking methods, finally arriving at a new conceptualization of the Internet space as the meteorological pressure system. This is an invitation to see the Internet and movements occurring within it from a new perspective: where temperatures rise and drop, winds blow and dissipate, fogs come and go; where limits of spatial characteristics are forming different climates; where each part affects the whole, and can potentially bring out various chain reactions. Such a conceptual system opens up the possibility to see the Internet as a coherent spatial structure, filled with becomings and intricate relationships.